2010
DOI: 10.1007/s11199-010-9864-5
|View full text |Cite
|
Sign up to set email alerts
|

Flirtatious Communication: An Experimental Examination of Perceptions of Social-Sexual Communication Motivated by Evolutionary Forces

Abstract: Guided by Relational Framing and Parental Investment Theories, this investigation examined experimentally induced flirtatious interactions. United States undergraduates (N=252) from the Mid-Atlantic region viewed a flirtatious interaction and rated a confederate on physical and social attraction, affiliation, dominance, and conversational effectiveness. Generally, it was hypothesized that different flirting motivations would lead to different evaluations of the flirters, and perceptions of flirters would vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…Thus, the lack of a sex difference challenges assumptions of universality in evolutionary psychology theories. Evidence of sex similarity also emerged in Frisby et al's (2010) study of the value placed on mating partners' affiliation. This study also found a sex difference such that women valued dominance more than men.…”
Section: Insights About Sex Differences and Similarities From Specialmentioning
confidence: 92%
See 4 more Smart Citations
“…Thus, the lack of a sex difference challenges assumptions of universality in evolutionary psychology theories. Evidence of sex similarity also emerged in Frisby et al's (2010) study of the value placed on mating partners' affiliation. This study also found a sex difference such that women valued dominance more than men.…”
Section: Insights About Sex Differences and Similarities From Specialmentioning
confidence: 92%
“…For example, Smith et al (2010) show the importance of intersectionality by demonstrating that lesbians value different psychological qualities in a mate than heterosexual men and women. Providing evidence of contextual influences, Frisby et al (2010) found that perceptions of flirtatiousness depended on the reasons that an actor was engaged in this behavior. For example, men flirting to attract a sexual partner were perceived as more dominant than men flirting to increase intimacy in a relationship.…”
Section: Methodological Issues Raised By Special Issuementioning
confidence: 99%
See 3 more Smart Citations